2016
DOI: 10.1038/srep25118
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma induces inflammation in the uterus through the γδ T/IL-17 pathway

Abstract: After insemination, a large number of leukocytes migrate into the uterus, which is accompanied by intense inflammation. However, the details of how seminal plasma interacts with the uterus are still not very clear. Here, we present that neutrophils migrate and accumulate around the uterine epithelium following insemination, which is accompanied by an increase in interleukin (IL) 17A levels. Additionally, we find that γδ T cells are the major source of IL-17A, and the seminal plasma could induce the γδ T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…Following insemination of naive mice, a large number of leukocytes migrate into the uterus accumulating around the uterine epithelium. The seminal plasma sensitizes the γδ T‐cells, which secrete IL17A, thereby inducing inflammation regulating the expression of different chemokines and cytokines (Song et al, ). This triggers the activation and expansion of T‐ and B‐lymphocytes and NK cells enhancing of cytokine expression, for example, IL2, IL4, and IFNA to mediate maternal tolerance at the implantation site (Johanson, Bromfield, Jasper, & Robertson, ).…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%
“…Following insemination of naive mice, a large number of leukocytes migrate into the uterus accumulating around the uterine epithelium. The seminal plasma sensitizes the γδ T‐cells, which secrete IL17A, thereby inducing inflammation regulating the expression of different chemokines and cytokines (Song et al, ). This triggers the activation and expansion of T‐ and B‐lymphocytes and NK cells enhancing of cytokine expression, for example, IL2, IL4, and IFNA to mediate maternal tolerance at the implantation site (Johanson, Bromfield, Jasper, & Robertson, ).…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%
“…In non-pregnant individuals, neutrophils can be found in the cervix, endometrium and fallopian tubes (65, 66) while in pregnant women neutrophils additionally invade the decidua, placenta, and fetal membranes (67,68). At insemination neutrophils specifically migrate and accumulate around the uterine epithelium (69). Here, they overtake various critical functions associated with angiogenesis, uSA remodeling and trophoblast invasion (70, 71) ( Figure 1D).…”
Section: Neutrophilsmentioning
confidence: 99%
“…Early studies suggested that IL‐17 was associated with complications during pregnancy and infertility . However, more recent studies suggest a beneficial function for IL‐17 during pregnancy including the promotion of embryo implantation . Importantly, new biologics targeting IL‐17A and its receptor have shown clinical efficacy in the treatment of psoriatic disease and rheumatoid arthritis .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, more recent studies suggest a beneficial function for IL-17 during pregnancy including the promotion of embryo implantation. [8][9][10] Importantly, new biologics targeting IL-17A and its receptor have shown clinical efficacy in the treatment of psoriatic disease and rheumatoid arthritis. 3 Given the prevalence of these diseases in the female population and the requirement for lifelong use of these medications to prevent disease progression, understanding the impact of this cytokine pathway on pregnancy is vital for reproductive health.…”
Section: Introductionmentioning
confidence: 99%